A systematic exploration of the interactions between bacterial effector proteins and host cell membranes - Weigele, Bethany A. (Nat Commun, 2017)
Membrane-bound organelles serve as platforms for the assembly of multi-protein complexes that function as hubs of signal transduction in eukaryotic cells. Microbial pathogens have evolved virulence factors that reprogram these host signaling responses, but the underlying molecular mechanisms are poorly understood. Here we test the ability of ~200 type III and type IV effector proteins from six Gram-negative bacterial species to interact with the eukaryotic plasma membrane and intracellular organelles. We show that over 30% of the effectors localize to yeast and mammalian cell membranes, including a subset of previously uncharacterized Legionella effectors that appear to be able to regulate yeast vacuolar fusion. A combined genetic, cellular, and biochemical approach supports that some of the tested bacterial effectors can bind to membrane phospholipids and may regulate membrane trafficking. Finally, we show that the type III effector IpgB1 from Shigella flexneri may bind to acidic phospholipids and regulate actin filament dynamics.